Scanning electron microscopy study of the choroid plexus in the monkey (Cebus apella apella) - Tamega, Oisenyl José [UNESP]; Tirapelli, Luís Fernando; Petroni, Sidnei (FapUNIFESP (SciELO), 2000)
The cells of the choroid plexus of the lateral ventricles of the monkey Cebus apella apella were examined through scanning electron microscopy at contributing to the description of such structures in primates. The animals were anesthetized previously with 3% hypnol intraperitoneally and after perfusion with 2.5% glutaraldehyde, samples of the choroid plexus were collected after exhibition of the central portion and inferior horn of the lateral ventricles. The ventricular surface of those cells presents globose form as well as fine interlaced protrusions named microvilli. Among those, it is observed the presence of some cilia. Resting on the choroid epithelial cells there is a variable number of free cells, with fine prolongations which extend from them. They are probably macrophages and have been compared to Kolmer cells or epiplexus cells, located on choroid epithelium. The choroid plexus of the encephalic lateral ventricles of the monkey Cebus apella apella at scanning electron microscopy is similar to that of other primates, as well as to that of other species of mammals mainly cats and rats, and also humans.
Keywords: Choroid plexus; Monkey; Scanning electron microscopy; animal; Cebidae; choroid plexus; histology; lateral brain ventricle; male; scanning electron microscopy; ultrastructure; Animals; Cebus; Choroid Plexus; Lateral Ventricles; Male; Microscopy, Electron, Scanning